Exploring the Influence of English Song Viewing on Second Language Acquisition: A Psycholinguistic Study - Lela Susanty; Aan Fatwa Setiawan; Ishak Bagea; Nyayu Yayu Suryani; Dian Heriani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The importance of English as a second language (L2) has heightened in the era of globalization, with individuals worldwide striving for proficiency in academic, professional, and social contexts. This study investigates the influence of watching English-language songs on L2 acquisition, with a particular focus on psycholinguistic aspects. Employing a qualitative descriptive approach, the data consists of words, phrases, and sentences extracted from selected songs such as